Pembinaan Iman Bagi Kaum Muda di Gereja Kristen Jawa Purwantoro, Wonogiri, Jawa Tengah dengan Tema “Menatap Hari Esok Bersama Yesus” - Epafras Mujono; Sri Sulistyowati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This article is the result of community service activities, with several background problems, namely: First, there is a need or desire from the administrators and members of the GKJ Purwantoro Local Youth Commission for a variety of speakers from outside the local church, in the context of Easter commemoration. Second, there is a need to strengthen faith and commitment to Jesus, for young people in places where service activities are carried out. The objectives that are expected to be achieved from this Community Service activity are as follows: First, to fulfill the needs of the young people of the GKJ Purwantoro for enthusiastic and firm or clear delivery of the Word of God, through a variety of lecturers or preachers from outside GKJ. Second, so that the spirit of faith and commitment to life of you young GKJ Purwantoro can be awakened and refreshed. The method used in delivering service material is the lecture method, while the method for presenting the results of this service is the descriptive method. The results of this service activity are: First, faith formation material with the theme